Pelatihan Orang Tua dalam Meningkatkan Kemandirian Anak Usia Dini Melalui Aktivitas Harian di Rumah - Aisyah; Hasiana, Isabella (PT. Cahya Edupreneur Indonesia, 2024)
This community service activity in the form of training for parents aims to provide insight and practical skills to parents in supporting the development of early childhood independence. The method used is a direct question and answer to parents regarding children's independence. The tools used to assist in the implementation of this community service activity are in the form of images and videos. The implementation of the activity is carried out through six methods, namely lecture and discussion methods, practical training and simulation, demonstration methods, group guidance, provision of modules and supporting media as well as evaluation and monitoring. This training was given to parents of 25 students of Pamiwahan Putra II Wahyu Luhur Kindergarten. As a result of this training, parents know and can adopt a more positive and consistent approach to educating children so that they can become more independent and ready to face challenges in the future. Full support from parents in this process is very important to shape the character of children who are independent, creative, and confident.